Pasture Recovery Period Affects Humic Substances and Oxidations of Organic Matter in Eastern Amazon - Carlos Augusto Rocha de Moraes Rego; Juan López de Herrera; Paulo Sérgio Rabello de Oliveira; Luciano Cavalcante Muniz; Jean Sérgio Rosset; Eloisa Mattei; Lucas da Silveira; Marinez Carpiski Sampaio; Marcos Gervasio Pereira; Karolline Rosa Cutrim Silva; Ismênia Ribeiro de Oliveira (Agronomy, 2024)
Land management practices that overlook soil limitations and potential have led to varying degrees of degradation. This study evaluates the carbon content in chemical and oxidisable soil fractions across different pasture recovery periods, comparing them to secondary forests. The management practices assessed include the following: secondary forest (SF), perennial pasture (PP), perennial pasture recovered five years ago (P5), and perennial pasture recovered eight years ago (P8), all on Plinthosols. We analysed carbon levels in oxidisable fractions and humic substances at depths of 0–0.10 m, 0.10–0.20 m, 0.20–0.30 m, and 0.30–0.40 m. The SF and P8 areas showed the highest organic matter content within the humic fractions, compared to the PP and P5 areas. Additionally, the P8 area demonstrated an increase in the labile and moderately recalcitrant fractions of organic matter, standing out among the different fractions evaluated. The multivariate principal component analysis indicated that P8 has the greatest impact on soil quality, followed by FS, P5, and PP. The pasture recovery over the past eight years has significantly improved soil carbon accumulation, highlighting the benefits of land restoration.